2006
DOI: 10.3892/ijmm.17.5.925
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin binding protein-1 is downregulated during polymicrobial sepsis in the rat

Abstract: Abstract.We have previously shown that administration of adrenomedullin (AM) and AM binding protein-1 (AMBP-1) in combination maintains cardiovascular stability and reduces mortality in a rat model of sepsis. However, it is unknown whether AMBP-1 is reduced under the septic condition and, if so, whether lipopolysaccharide (LPS) plays a role in downregulating AMBP-1. To determine this, male adult SpragueDawley rats were subjected to either polymicrobial sepsis by cecal ligation and puncture (CLP), or endotoxemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The hepatic production and plasma concentration of AMBP-1 is dramatically reduced by over 50% during the late phase of cecal ligation and puncture (CLP)-induced sepsis in rats (12) and represents the pathophysiologic mechanism by which AM loses the ability to maintain its vasoactive function (9,10). The administration of AM and AMBP-1 in combination protects against cardiovascular instability and mortality in experimental sepsis by preventing the increase in peripheral vascular resistance and maintaining oxygen delivery to terminal organs.…”
Section: Adrenomedullin (Am)mentioning
confidence: 99%
“…The hepatic production and plasma concentration of AMBP-1 is dramatically reduced by over 50% during the late phase of cecal ligation and puncture (CLP)-induced sepsis in rats (12) and represents the pathophysiologic mechanism by which AM loses the ability to maintain its vasoactive function (9,10). The administration of AM and AMBP-1 in combination protects against cardiovascular instability and mortality in experimental sepsis by preventing the increase in peripheral vascular resistance and maintaining oxygen delivery to terminal organs.…”
Section: Adrenomedullin (Am)mentioning
confidence: 99%
“…In light of this report, it is plausible that AMBP-1 exerts its effects on AM by preventing the cleavage of AM by metalloproteinases. Recently we have shown that in a rat model of sepsis or endotoxemia, AMBP-1 gene and protein expression of hepatic tissue was significantly downregulated in the late phase of sepsis [19]. Even though AM is upregulated during sepsis primarily due to elevated levels of LPS [26], the vascular response to AM is significantly reduced in late sepsis [12].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the administration of LPS to normal Sprague-Dawley rats downregulates AMBP-1 production in the liver [19]. Since hepatocytes are the primary source of AMBP-1 biosynthesis in the liver, a co-culture strategy using hepatocyte and Kupffer cells were employed to determine whether LPS directly or by increasing pro-inflammatory cytokines from Kupffer cells downregulates AMBP-1 production.…”
Section: Lps Treatment In Co-culture Of Hepatocytes and Kupffer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in vitro addition of AMBP-1 can completely restore AM hyporesponsiveness in the isolated blood vessels in a dose-response fashion (28). Although plasma levels of AM increase in sepsis (37), the levels of AMBP-1 decreased significantly in the blood and tissues under such conditions (28,52). The AM hyporesponsiveness observed in sepsis may be caused by the reduced AMBP-1 production.…”
Section: Discussionmentioning
confidence: 99%